Success factors of long-term CIOs - Patrick Hillebrand; Markus Westner (Information Systems and e-Business Management, 2021)
Although the average tenure of CIOs has increased over the last years, the majority of CIOs have been in their positions for only three years or less. Nevertheless, some CIOs have been successful in their position for a long time. In this study, we use tenure as a proxy for success as a CIO. The goal of this paper is to examine factors that are critical to the success of long-term CIOs. For this purpose, we created and analyzed resumes of 384 CIOs. Out of these 384, we conducted 19 interviews with CIOs from top-tier companies and collected and analyzed both qualitative and quantitative data. In the process, we were able to identify nine factors that are critical for the success (CSF) of CIOs. These factors fall into three categories. Category “Personality” includes “Accepting and embracing change” (CSF #1), “Being perseverant to pursue long-term goals” (CSF #2), “Anticipating the future through visionary thinking” (CSF #3), and “Being empathetic to deal with uncertainty felt by co-workers” (CSF #4). The “Role Fulfilment” category includes “Cross-functional involvement and integration of the IT organization” (CSF #5), “Positioning and restructuring of the IT organization” (CSF #6), and “Well-connected and communicative leadership” (CSF #7). The “Organizational Environment” category consists of “Availability of skilled workforce” (CSF #8) and “Reporting line to the CEO” (CSF #9). CSFs 1, 2, and 3 were perceived as most important by the participating CIOs. The results may be of particular interest both to aspiring CIOs and equally their employing organizations, as they reflect what long-term CIOs value during their time in office.
Keywords: 650; Chief information officer; CIO tenure; Critical success factors; CIO roles; Interview-based exploratory mixed-method study